Tinkering with the C-Function: A Molecular Frame for the Selection of Double Flowers in Cultivated Roses - Annick Dubois; Olivier Raymond; Marion Maene; Sylvie Baudino; Nicolas B. Langlade; Véronique Boltz; Philippe Vergne; Mohammed Bendahmane (2010)
Roses have been cultivated for centuries and a number of varieties have been selected based on flower traits such as petal form, color, and number. Wild-type roses have five petals (simple flowers), whereas high numbers of petals (double flowers) are typical attributes of most of the cultivated roses. Here, we investigated the molecular mechanisms that could have been selected to control petal number in roses.